1995
DOI: 10.1097/00004872-199512010-00034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arginine vasopressin and 1-desamino-8-D arginine vasopressin on forearm vasculature of healthy subjects and patients with a V2 receptor defect

Abstract: Objectives: To assess which vasopressin receptor subtype mediates the vasodilation occurring in response to arginine vasopressin and 1-desamino-8-D (DD)-argtnine vasopressin and whether nitric oxide is involved in these effects.Materials and methods: Vasoactive effects of arginine vasopressin and DD-arginine vasopressin on forearm vasculature were studied in healthy subjects and in patients with congenital nephrogenic diabetes insipidus with a vasopressin type 2 (V 2) receptor gene defect. Venous occlusion ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 8 publications
2
20
0
Order By: Relevance
“…However, a number of studies have now well documented the existence of extrarenal V2 receptors, probably located on the vascular endothelium (29). The stimulation of these receptors by V2 agonists results in a significant vasodilation (30,31) that probably accounts for the fall in BP observed in this study (20,22).…”
Section: Discussionsupporting
confidence: 52%
“…However, a number of studies have now well documented the existence of extrarenal V2 receptors, probably located on the vascular endothelium (29). The stimulation of these receptors by V2 agonists results in a significant vasodilation (30,31) that probably accounts for the fall in BP observed in this study (20,22).…”
Section: Discussionsupporting
confidence: 52%
“…However, similar hemodynamic effects of desmopressin administration have been described in patients with central diabetes insipidus, who lack endogenous vasopressin 10,19 and therefore an antagonism of vasopressin on vascular V 1 receptors is unlikely. By contrast, patients with Xlinked nephrogenic diabetes insipidus, who lack the V 2 receptor-mediated renal antidiuretic response to desmopressin, 20 manifest no increase in coagulation factors 10,12 and show no vasodilatation in response to desmopressin, 10,11 thus suggesting that the absence of responses to desmopressin is a consequence of an extrarenal V 2 receptor defect. In the present experiments, desmopressin caused dilatation in the absence of vasopressin and in the presence of selective V 1 receptor antagonists (peptidic and nonpeptidic).…”
Section: Discussionmentioning
confidence: 98%
“…In agreement with the present results, experiments in healthy subjects indicate that L-NMMA, another nitric oxide synthase inhibitor, did not modify the increase in forearm blood flow induced by desmopressin, thus suggesting that the desmopressin-induced vasodilatation is mediated by mechanisms other than endothelial nitric oxide. 11 The involvement of prostanoids in the modulation of the desmopressin dilator response was assessed by pretreatment of the arterial segments with the cyclooxygenase inhibitor indomethacin. The results showed that indomethacin inhibits the desmopressin-induced relaxation, thus suggesting that the effect is largely due to the release of dilating prostaglandins from renal arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, complex specific tissue interactions were shown between V2 and V1a effects, at the epithelial and vascular levels (25). Acute regional vasodilator and hypotensive effects of dDAVP mediated by endothelial V2R and NO production have been reported in healthy humans and animals (15,45,97,101,103).…”
Section: Water Conservation and Blood Pressure: Pathophysiological Obmentioning
confidence: 99%